Cultural histories of law, media and emotion
1 online resource (xvii, 272 pages)
Keywords: "Cultural Histories of Law, Media and Emotion: Public Justice explores how the legal history of a long-eighteenth-century Britain has been transformed by the cultural turn, and especially the associated history of emotion. This volume is the ideal resource for upper-level undergraduates, postgraduates, and scholars interested in the history of emotions as well as the legal history of Britain from the late seventeenth to the nineteenth century"--